Nationwide assessment of coastal sea level and shoreline dynamics in Malaysia using Geospatial Technology and Machine Learning - IDOWU, NAHEEM ADEBISI (2021)
This study aims to conduct a holistic evaluation of the current and future trend in coastal sea level and shoreline dynamics along Malaysia coastline using geospatial technology and machine learning models